Sejarah Pemikiran Dakwah Islam Isa Anshary Tahun 1940-1969 - Yusril Fahmi Adam (Historia Madania: Jurnal Ilmu Sejarah, 2022)
This article aims to reconstruct the history of Isa Anshary's Islamic da'wah thought which is still not widely found in Islamic historiography in Indonesia. This study uses an intellectual history approach (intellectual history) and historical actor theory. The method used in this study is the historical method through four stages, namely data collection or sources (heuristics), source criticism, interpretation and historiography. Based on the historical approach, theory, and method used, this research is not only descriptive-narrative, but also analytical-descriptive by elaborating the sources obtained. The results of this study indicate that Isa Anshary was a scholar who throughout his life struggled for the da'wah of Islam. Isa Anshary's Islamic da'wah thought is complex and integral to aspects of human life. That is, the arena of da'wah is not limited to just inviting ritual worship, but must enter other aspects such as education, economics, and even politics. Isa Anshary's Islamic da'wah can be analyzed through his da'wah activities when he was the general chairman of the Islamic Union (Persis) and the Masyumi Party. In Persis and Masyumi, the Islamic da'wah delivered by Isa Anshary is not just a word that is conveyed, but is implemented with action, so that the thoughts and attitude of the da'wah shown by Isa Anshary have a great influence on Muslims for socio-religious and political in post-independence Indonesia.Keywords: Da'wah, Isa Anshary, Islam.